Opportunistic Use of CT Imaging for Osteoporosis Screening and Bone Density Assessment: A Qualitative Systematic Review - Gausden, Elizabeth B; Nwachukwu, Benedict U; Schreiber, Joseph J; Lorich, Dean G; Lane, Joseph M (Journal of bone and joint surgery. American volume, 2017)
The purpose of this study was to determine the clinical opportunities for the use of computed tomography (CT) imaging for inferring bone quality and to critically analyze the correlation between dual x-ray absorptiometry (DXA) and diagnostic CT as reported in the literature. A systematic review of the MEDLINE database was performed in February 2016 using the PubMed interface. The inclusion criteria were English language, studies performed using living human subjects, studies pertaining to orthopaedics, use of conventional diagnostic CT scans, studies that measured cancellous bone, and studies that reported Hounsfield unit (HU) measurements directly rather than a computed bone mineral density. Thirty-seven studies that reported on a total of 9,109 patients were included. Of these, 10 studies correlated HU measurements of trabecular bone with DXA-based bone assessment. Reported correlation coefficients ranged between 0.399 and 0.891, and 5 of the studies reported appropriate threshold HU levels for diagnosing osteoporosis or osteopenia. Direct HU measurement from diagnostic CT scans has the potential to be used opportunistically for osteoporosis screening, but in its current state it is not ready for clinical implementation. There is a lack of exchangeability among different machines that limits its broad applicability. Future research efforts should focus on identifying thresholds at specific anatomic regions in high-risk patients in order to have the greatest impact on patients. However, using diagnostic CT to infer region-specific osteoporosis could be extraordinarily valuable to orthopaedic surgeons and primary care physicians, and merits further research.